A torque sharing function with online compensation of excitation current control method for torque ripple reduction in electric excitation auxiliary switched reluctance motor drives. Issue 8 (22nd April 2022) - Meng, Fangui; Liu, Aimin; Lou, Jiachuan; Zhang, Wenpeng; Ren, Da; Li, Yingsa
Abstract: A torque sharing function (TSF) with online compensation of excitation current control method is proposed for torque ripple reduction in electric excitation auxiliary switched reluctance motor (SRM) drives, which mitigates the problem of severe torque ripple inherent in traditional TSF control during the commutation of armature winding. The torque formula of the motor is derived and the finite element analysis of the static torque under different excitation currents is carried out, which proves that the output torque can be changed by adjusting the excitation current. Therefore, the proposed method is based on cosine TSF control, which uses a sliding mode control algorithm to adjust the amplitude of the excitation current to online compensate the torque fluctuations during commutation. Besides, Simulink, Simplorer and Maxwell co‐simulation and experiments are carried out on the traditional TSF control and the proposed method. The results demonstrate that the proposed method is superior to the traditional TSF control and the electric excitation auxiliary SRM has better torque performance and smaller torque ripple under the proposed method.